2008
DOI: 10.1210/en.2008-0817
|View full text |Cite
|
Sign up to set email alerts
|

The Pairing of a Selective Estrogen Receptor Modulator, Bazedoxifene, with Conjugated Estrogens as a New Paradigm for the Treatment of Menopausal Symptoms and Osteoporosis Prevention

Abstract: The menopausal transition is associated with decreased ovarian function and concomitant decline in estrogen production, which may result in physiological effects such as hot flashes, reduced bone mass, and altered lipid profile. It is well established that these unfavorable changes are effectively offset with estrogen therapy (ET) or, in women with a uterus, estrogens in combination with a progestin (hormone therapy). Selective estrogen receptor (ER) modulators (SERMs), which exhibit both ER agonist and antago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 35 publications
2
104
0
2
Order By: Relevance
“…Preclinical data have suggested that the combination treatment of bazedoxifene and conjugated estrogens (CE) might lead to a more favorable benefit-risk profile in the treatment of menopause symptoms, including favorable vasomotor, lipid, and skeletal response with minimal stimulation in the uterus (Kharode et al, 2008;Peano et al, 2009). This combination therapy also shows efficacy in the treatment of osteoporosis in a manner that prevents uterine growth, with decreased uterine wet weight and lower cholesterol levels .…”
Section: Nuclear Receptors and Their Selective Modulatorsmentioning
confidence: 99%
“…Preclinical data have suggested that the combination treatment of bazedoxifene and conjugated estrogens (CE) might lead to a more favorable benefit-risk profile in the treatment of menopause symptoms, including favorable vasomotor, lipid, and skeletal response with minimal stimulation in the uterus (Kharode et al, 2008;Peano et al, 2009). This combination therapy also shows efficacy in the treatment of osteoporosis in a manner that prevents uterine growth, with decreased uterine wet weight and lower cholesterol levels .…”
Section: Nuclear Receptors and Their Selective Modulatorsmentioning
confidence: 99%
“…A tissue-selective estrogen complex (TSEC) partners bazedoxifene (BZA), a novel estrogen agonist/antagonist, with conjugated estrogens (CE), with the goal of designing a novel menopausal therapy that combines the beneficial effects of both [28]. Ideally, a TSEC would relieve menopausal symptoms such as hot flushes and vaginal atrophy, prevent osteoporosis, and have a favorable safety and tolerability profile, including a neutral effect on the breast and uterus.…”
Section: Tissue-selective Estrogen Complexmentioning
confidence: 99%
“…Ideally, a TSEC would relieve menopausal symptoms such as hot flushes and vaginal atrophy, prevent osteoporosis, and have a favorable safety and tolerability profile, including a neutral effect on the breast and uterus. BZA is a novel estrogen agonist/antagonist that has shown efficacy in preventing fractures and preserving bone mineral density (BMD) in postmenopausal women, without any evidence of endometrial or breast stimulation [28], [ …”
Section: Tissue-selective Estrogen Complexmentioning
confidence: 99%
“…(Stovall & Pinkerton, 2008) Preclinical studies have shown that bazedoxifene antagonizes estrogen-induced uterine and mammary gland stimulation more effectively than other SERMs like raloxifene and lasofoxifene. (Peano et al, 2009;Kharode et al, 2008) A randomized, double-blind, placebocontrolled Phase III trial in 3,397 postmenopausal women examined the effect of bazedoxifene 10, 20, or 40 mg combined with conjugated estrogens 0.625 mg or 0.45 mg on bone and endometrium. In this trial, the bazedoxifene plus conjugated estrogen combination therapy showed a statistically significant increase in BMD and a decrease in bone biochemical turnover markers compared with placebo.…”
Section: Bazedoxifene and Conjugated Estrogen Combination Therapymentioning
confidence: 99%